ABORDAGEM DA EDUCAÇÃO AMBIENTAL NO ENSINO DE QUÍMICA: UMA ANÁLISE A PARTIR DE ARTIGOS PUBLICADOS NA REVISTA QUÍMICA NOVA NA ESCOLA (QNEsc) - Sergiana S. de Oliveira Aprigio; Maria Vitória L. Nascimento; Leonardo B. Cantanhede; Severina C. da Silva Cantanhede; Osiel C. da Trindade Junior; Douglas R. e Silva Barbosa; Lidiane da Silva Araújo (Química Nova)
The knowledge of chemistry connected to environmental problems and sustainable development can provide an opportunity for dynamic, investigative, and directed teaching towards the recognition of chemistry itself as a science and social practice. From this perspective, this work aimed to investigate how discussions involving topics related to environmental education are conducted by researchers and/or professionals in chemical education, based on articles published in the journal Química Nova na Escola (QNEsc). The selection of articles was made considering publications from QNEsc between the years 1995 and 2022, focusing on terms such as environmental education, environment, pollution, environmental aspects, sustainability, and sustainable development present in the title, abstract, and/or keywords of the published articles. The selected texts were analyzed using Iramuteq software, applying correspondence factorial analysis (CFA), hierarchical descendant classification (HDC), similarity analysis, and word cloud using their respective abstracts. The data show that topics such as water, pesticides, waste, and plastic materials (polymers) were the most addressed by the publications, indicating a path that seeks to present and discuss proposals that value the need for sustainable actions, addressing environmental issues that directly impact the way humans use natural resources in the present and future.